Acute and delayed biochemical, hematological, and neuromuscular responses to the Rest-pause resistance training method. Issue 2 (3rd April 2021) - Azevedo, Antenor Barbosa Calandrini de; Penna, Eduardo Macedo; Costa, Andrea Silvestre Lobão; Martins Filho, Arnaldo Jorge; Franco, Edna Cristina Santos; Coswig, Victor Silveira
ABSTRACT: Objective: This investigation aimed to compare acute and delayed biochemical, hematological, and neuromuscular responses to the Rest-pause (RP) method and traditional resistance training (TRT) through 48 h. Methods: This crossover design study, in which the training sessions were separated by a 7-days washout interval. Twelve recreationally trained males (age: 22.4 ± 1.8 years) realized the RP protocol, consisting of two sets of 6-3-3 repetitions at 90% of 6-repetition maximum (6RM) and 20 s of rest between repetitions and 2:30 min between sets and TRT protocol, consistent of 3 sets of 8 repetitions at 85% of 6RM with 2 min between sets. Blood analyses and neuromuscular performance were measured before (PRE), immediately after (POST) and 24 (24H) and, 48 h (48H) after protocols. Results: Regarding between-moments comparisons, biochemical and hematological responses increased after protocols ( p < 0.05) and returned the baseline values after 24H ( p > 0.05). Only creatine kinase, aspartate aminotransferase, neutrophiles, and white blood cells increased after protocols ( p < 0.05) and returned to baseline values after 48H ( p > 0.05). No significant difference between moments was found for neuromuscular performance ( p > 0.05). Regarding difference between groups, red blood cells and hemoglobin showed lower values for the RP in comparison to the TRT after 24H ( p = 0.03). Conclusion: The sets configurations seem to be insufficient to induce an additional effect in muscle damage markers, immune responses, and neuromuscular performance. Finally, it seems that advanced techniques with lower volume don't affect the immune system for long time periods.